RETRACTED: Algorithm and software tools for optimizing the preparation of routes on high-speed lines based on RFID technology - Aliev Ravshan; Aliev Marat; Tokhirov Ezozbek (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001